Traffic Anomaly Detection Algorithm for Wireless Sensor Networks Based on Improved Exploitation of the GM(1, 1) Model. (14th July 2016) - Yu, Qin; Lyu, Jibin; Jiang, Lirui; Li, Longjiang
As WSNs gain popularity, they are becoming more and more necessary for traffic anomaly detection. Because worms, attacks, intrusions, and other kinds of malicious behaviors can be recognized by traffic analysis and anomaly detection, WSN traffic anomaly detection provides useful tools for timely reaction and appropriate prevention in network security. In the paper, we improve exploitation of GM(1, 1) model to make traffic prediction and judge the traffic anomaly in WSNs. Based on our systematical researches on the characteristics of WSN traffic, the causes of WSN abnormal traffic, and latest related research and development, we better exploit the GM(1, 1) model following four guidelines: using a sliding window to determine historical data for modeling, optimizing initial value of one-order grey differential equation, making traffic prediction by short step exponential weighted average method, and judging whether the traffic of the next moment is abnormal by Euclidean distance. Then, we propose a traffic anomaly detection algorithm for WSNs based on the improved exploitation of GM(1, 1) model. Simulation results and comparative analyses demonstrate that our proposed WSN traffic anomaly detection algorithm can reduce the undetected rate and has better anomaly detection accuracy than traditional traffic anomaly detection algorithms.